Phenoconversion of CYP3A4, CYP2C19 and CYP2D6 in Pediatrics, Adolescents and Young Adults With Lymphoma: Rationale and Design of the PEGASUS Study - Rachel Conyers; Tayla Stenta; Andrew A. Somogyi; Carl Kirkpatrick; Andreas Halman; Sophie Wang; Claire Moore; Dhrita Khatri; Elizabeth Williams; Roxanne Dyas; Tim Spelman; David A. Elliott; et al. (Clinical and Translational Science)
ABSTRACT Phenoconversion is the discrepancy between genotype‐predicted phenotype and clinical phenotype, due to nongenetic factors. In oncology patients, the impact of phenoconversion on drug selection, efficacy, toxicity, and treatment outcomes is unknown. This study will assess acceptability and feasibility of investigating phenoconversion using probe medications in a pediatric and adolescent and young adult (AYA) oncology population. This prospective, single‐arm, single‐blind, nonrandomized feasibility study, will enroll individuals aged 6–25 years with a new diagnosis of Hodgkin Lymphoma or Non‐Hodgkin Lymphoma. Genotyping will be performed at baseline using whole genome sequencing or targeted panel testing. Longitudinal phenotyping will be conducted throughout the cancer treatment using exogenous oral enzyme‐specific probes, specifically subtherapeutic dextromethorphan (CYP2D6) and omeprazole (CYP2C19, CYP3A4) for enzyme activity assessment. The primary outcome measure will be the proportion of patients who consent to the study and successfully complete baseline and at least two longitudinal time points with valid probe drug metabolic ratio measurements. Secondary outcomes include classification of clinical phenotypes based on probe drug metabolic ratios, probe drug safety, barriers to consent, acceptability of pharmacogenomic and phenoconversion testing, longitudinal genotype/phenotype concordance, inflammatory profiles, and patient and disease factors influencing phenoconversion. The trial has received ethics approval (2023/ETH1954) and is registered at ClinicalTrials.gov (NCT06383338). Findings will be disseminated through peer‐reviewed publications and professional conferences, providing critical insights to advance the understanding of phenoconversion in oncology from pediatrics to adults. These results will help shape future research and drive the implementation of more personalized precision medicine strategies for all people with cancer.